Analysis of Creative Thinking and Curiosity in X Class Students - Rahmayani, Bulan; Junaedi, Iwan; Walid, Walid; Susilo, Bambang Eko (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2023)
In the learning, because the learning time isn’t sufficient to convey material, teacher who concerned learning results than learning process made students just imitating teachers’ problem solving. They aren’t trained to solve new problems. This research aims, (1) finds out the mathematics creatie thinking ability of high school students; (2) finds out the characters of the students’ curiosity; (3) finds out the influence of curiosity on students’ creative thinking ability. This research method and design is a quantitative and comparison of approaches. The research is conducted at one of the state high schools in Semarang. The research population sample in a row is all students of classes of X MIPA and X MIPA 3. This population is given a creative thinking ability test. This sample is given a curiosity questionnaire. Creative thinking ability mean of the ten classes of X MIPA is 69,4. Curiosity mean of X MIPA 3 is 169,3. Therefore, (1) students’ mathematics creative thinking ability is not optimal; (2) the character of the students’ curiosity is not optimal; (3) curiosity positively affects creative thinking ability. That resulted in teacher developing learning media and processes and students’ curiosity to their students’ creative thinking ability.Dalam pembelajaran, karena waktu pembelajaran tidak mencukupi untuk menyampaikan materi, guru mengutamakan hasil dari pada proses pembelajaran mengakibatkan siswa meniru proses pemecahan masalah dari guru dan tidak terlatih menyelesaikan masalah baru. Tujuan penelitian, (1) mengetahui kemampuan berpikir kreatif matematis siswa SMA; (2) mengetahui karakter rasa ingin tahu siswa; (3) mengetahui pengaruh karakter rasa ingin tahu terhadap kemampuan berpikir kreatif siswa. Penelitian menggunakan metode penelitian kuantitatif. Desain penelitian adalah comparison of approaches. Penelitian awal dilaksanakan di salah satu SMA Negeri di Semarang. Populasi dan sampel penelitian berturut-turut adalah seluruh siswa kelas X MIPA dan X MIPA 3. Populasi diberikan tes kemampuan berpikir kreatif. Sampel diberikan angket curiosity. Rata-rata kemampuan berpikir kreatif dari 10 kelas X MIPA adalah 69,4. Rata-rata rasa ingin tahu siswa kelas X MIPA 3 adalah 169,3. Kesimpulannya (1) kemampuan berpikir kreatif matematis siswa belum optimal dalam pembelajaran, karena guru menyusun pembelajaran matematika belum terfokus pada kemampuan berpikir kreatif; (2) karakter rasa ingin tahu siswa belum optimal; dan (3) karakter rasa ingin tahu berpengaruh positif terhadap kemampuan berpikir kreatif. Hasil penelitian mengakibatkan guru mengembangkan curiosity dan media serta proses pembelajaran siswa untuk menumbuhkan kemamampuan berpikir kreatif mereka.